IS THE TIME OF RESPONSE A FACTOR THAT DETERMINES THE BRAND RECALL/IMAGE? - Fischer, Laura; Zamora, Oscar; Chavez, David (European Scientific Journal, ESJ, 2014)
Branding aims to establish a significant and differentiated presence in the market that attracts and retain loyal customers. Hence,some of the elements for the brand awarenessarethe use of highly emotional images and the time of exposure of the announcement. In this experimental study, the main purpose was to determine if there is a relationship between the time of response and the brand recall on affective images (IAPS). However, one hundred and forty eight (148) students from universities in Mexico City participated in this study, and the results suggested that the time of response is not a factor that determines the brand recall.